Comparative platelet proteome analysis reveals an increase of monoamine oxidase-B protein expression in Alzheimer's disease but not in non-demented Parkinson's disease patients - Zellner, Maria; Bugert, Peter (Journal of proteomics, 2012)
Monoamine oxidase-B (Mao-B) catalysing the breakdown of the neurotransmitter dopamine, is known to be involved in the pathophysiology of Parkinson's (PD) and Alzheimer's disease (AD). Increased brain Mao-B activity is associated with AD. This alteration can also be seen in platelets, albeit the cause has hitherto remained elusive. To gain a deeper understanding of the etiology of AD, the platelet proteome was characterised, (2D DIGE pH6-9, including Mao-B) from 150 individuals: 34AD, 13 vascular dementia, 15 non-demented PD patients, 49 matched controls, 18 oldest old and 21 young individuals. One significant change was noted after applying false discovery rate with the upregulation of the Mao-B expression (30% adjusted P value<0.001; effect size 1.31) in AD compared to age- and sex-matched controls. In contrast, Mao-B levels were unchanged in PD to matched controls. Western blot and mRNA analyses verified these findings. Moreover, Mao-B concentration correlated with age in the cognitive healthy individuals (r=0.53; P<0.001) and PD patients but not in those suffering from AD (r=−0.03; P=0.874). Mao-B activity correlated with the increased Mao-B protein expression in AD (r=0.81; P=0.016). We suggest that Mao-B platelet protein level may serve as a biomarker for age-related dementia, especially AD.